Median serum IgE levels to Culicoides recombinant (r-)allergens. - Jasmin Birras (11707271); Samuel J. White (10512181); Sigridur Jonsdottir (1303788); Ella N. Novotny (11707274); Anja Ziegler (11707277); A. Douglas Wilson (11707280); Rebecka Frey (3362939); Sigurbjörg Torsteinsdottir (11707283); Marcos Alcocer (8212260); Eliane Marti (157764) (2021)
Median serum IgE levels in fluorescence arbitrary units to Culicoides recombinant (r-) allergens in horses imported from Iceland to Switzerland that developed insect bite hypersensitivity (IBH) or remained healthy (H), and in horses living in Iceland (unexposed). Serum samples were taken the summer of clinical onset of IBH (T IBH ) and at the corresponding time in the H group. Same superscript letters indicate statistically significant differences in Kruskal-Wallis Z-value test (Dunn’s test) with Bonferroni correction for multiple comparisons. (DOCX)